2013
DOI: 10.14704/nq.2013.11.4.664
|View full text |Cite
|
Sign up to set email alerts
|

Human Consciousness: A Theoretical Prospective on Repetitive DNA Base Pairs Relation to Psychological Behavior

Abstract: In this paper an attempt has been made to bridge the gap between the repetitive Deoxyribonucleic acid (DNA) base pair sequences and psychological human behavior. Assuming the brain as a perfect fluid, the DNA coefficient between the biological and non-biological forms of the brain is calculated. These calculations are based on the Friedman density equations that describe the expansion or contraction of the universe in homogeneous and isotropic way in physical cosmology (only time independent equation is consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is reported that Adenine has an unexpectedly variable range of ionization energies along its reaction pathways which suggested that understanding experimental data on how Adenine survives exposure to UV light is much more complicated than the existing available data; these findings will have definite implications for experimental spectroscopic measurements of heterocyclic compounds. Based on above theories and observations the following modified DNA non-base pair model (Kumar et al, 2013) is suggested in this paper.…”
Section: Conjecturementioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that Adenine has an unexpectedly variable range of ionization energies along its reaction pathways which suggested that understanding experimental data on how Adenine survives exposure to UV light is much more complicated than the existing available data; these findings will have definite implications for experimental spectroscopic measurements of heterocyclic compounds. Based on above theories and observations the following modified DNA non-base pair model (Kumar et al, 2013) is suggested in this paper.…”
Section: Conjecturementioning
confidence: 99%
“…The genome sequence information is to be collected from 0 to 30 at the rate from 30 years onwards till death, the DNA sequence information is to be recorded. The modified (Kumar et al, 2013) DNA single molecule model is given in Table 2. 80 ears A-A (non Watson -Crick sequence) *indicates the mechanism of frequency resonance interactions are to be studied in depth using Quantum physics concept of light particle neutrino -neutrino interactions.…”
Section: Conjecturementioning
confidence: 99%